PENGARUH PERSONALITI MEREK TERHADAP MINAT BELI TAS ESGOTADO DENGAN KEPERCAYAAN MEREK SEBAGAI VARIABEL INTERVENING - Herwin, Herwin; Mariah, Mariah (Economic Faculty, Attahiriyah Islamic University, 2019)
This study aims to analyze the influence of brand’s personality on purchase intention with Brand Trust as an Intervening Variable on Esgotado Bag. This research is quantitative using data collection methods of questionnaires and observations in stores and studios of Esgotado Bags. Data analysis techniques use Structural Equation Modeling (SEM) as a data processing model. This research is expected to understand the influence of brand's personality on purchase intention with brand trust as an intervening variable. The result of this research is that Brand Personality has an effect on Buying Interest, Brand Trust Affects the Intention to Buy Esgotado’s bag, Brand’s Personality has no effect on Intention to Buy Esgotado’s bag. Keywords: brand, personality, trust, intention, purchase.